The effectiveness of emotionally focused couple therapy on heartbreak and marital conflict of couples - Ghasemi, Farahnaz; Afsharineya, Karim; Amiri, Hassan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this research was to Investigating the effectiveness emotionally focused couple therapy on heartbreak and marital conflict of couples. Method: The research method was semi-experimental with a pre-test, post-test and follow-up design with a control group and the statistical population was couples who referred to Azarshahr Psychology Clinic in Kermanshah in 1401. A sample of 20 people was selected by random sampling and randomly replaced in the experimental group and the control group. The measurement tools were Marital Conflict Questionnaire (MCQ-R) and Pines Marital Distress Scale (2001). The emotional-oriented couple therapy program of Jansen and Grayman (2006) was observed in 11 sessions, each session lasting 70 minutes for the experimental group and the control group. SPSS-26 software and mixed variance analysis with three-stage repeated measures were used for statistical analysis of the data. Results: Based on the findings, emotional couple therapy was effective in reducing marital conflicts (F=6.34, P=0.031) and marital boredom (F=5.61, P=0.048) and this effect was reported to be stable in the follow-up phase. (P=0.05). Conclusion: The results of this research, in addition to benefiting the couples participating in this research, can be used in the treatment decisions of psychologists, the training of treatment protocols in universities, the preparation and compilation of media and cultural programs to promote mental health in the media.